YY1 DNA binding and interaction with YAF2 is essential for Polycomb recruitment - Basu, Arindam (Oxford University Press, 2014)
Polycomb Group (PcG) proteins are crucial for epigenetic inheritance of cell identity and are functionally conserved from Drosophila to humans. PcG proteins regulate expression of homeotic genes and are essential for axial body patterning during development. Earlier we showed that transcription factor YY1 functions as a PcG protein. YY1 also physically interacts with YAF2, a homolog of RYBP. Here we characterize the mechanism and physiologic relevance of this interaction. We found phenotypic and biochemical correction of dRYBP mutant flies by mouse YAF2 demonstrating functional conservation across species. Further biochemical analysis revealed that YAF2 bridges interaction between YY1 and the PRC1 complex. ChIP assays in HeLa cells showed that YAF2 is responsible for PcG recruitment to DNA, which is mediated by YY1 DNA binding. Knock-down of YY1 abrogated PcG recruitment, which was not compensated by exogenous YAF2 demonstrating that YY1 DNA binding is a priori necessary for Polycomb assembly on chromatin. Finally, we found that although YAF2 and RYBP regulate a similar number of Polycomb target genes, there are very few genes that are regulated by both implying functional distinction between the two proteins. We present a model of YAF2-dependent and independent PcG DNA recruitment by YY1.